2007
DOI: 10.1038/sj.bjc.6604112
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical categorisation of ductal carcinoma in situ of the breast

Abstract: The aim of this study is to analyse whether immunohistochemistry (IHC) applying a broad set of markers could be used to categorise ductal carcinoma in situ (DCIS) of the breast in distinct subgroups corresponding to the recently defined molecular categories of invasive carcinoma. Immunohistochemistry of pure DCIS cases constructed in tissue arrays was performed with 16 markers (oestrogen receptor (ER), progesterone receptor (PR), androgen receptor (AR), Bcl-2, p53, Her2, insulin-like growth factor receptor, E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
76
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 19 publications
11
76
0
8
Order By: Relevance
“…HER2 overexpression seems to be most significant in high-grade DCIS, in which its prevalence is nearly 75% (17). In contrast to this relatively higher prevalence of HER2 overexpression in DCIS, the prevalence of marker expression indicative of the basal-like subtype is relatively lower in DCIS compared with IDC (1,3,4,17,18).…”
Section: Interlesional Heterogeneity Of Premalignant Lesionsmentioning
confidence: 53%
See 2 more Smart Citations
“…HER2 overexpression seems to be most significant in high-grade DCIS, in which its prevalence is nearly 75% (17). In contrast to this relatively higher prevalence of HER2 overexpression in DCIS, the prevalence of marker expression indicative of the basal-like subtype is relatively lower in DCIS compared with IDC (1,3,4,17,18).…”
Section: Interlesional Heterogeneity Of Premalignant Lesionsmentioning
confidence: 53%
“…An increased prevalence of HER2 protein overexpression (and gene amplification) in DCIS versus IDC has been confirmed in a number of subsequent studies (1,(16)(17)(18). HER2 overexpression seems to be most significant in high-grade DCIS, in which its prevalence is nearly 75% (17). In contrast to this relatively higher prevalence of HER2 overexpression in DCIS, the prevalence of marker expression indicative of the basal-like subtype is relatively lower in DCIS compared with IDC (1,3,4,17,18).…”
Section: Interlesional Heterogeneity Of Premalignant Lesionsmentioning
confidence: 78%
See 1 more Smart Citation
“…[101][102][103][104][105][106][107] However, it should be noted that its prevalence is lower than that of invasive triplenegative and basal-like breast cancers and that triple-negative and basal-like cancers often lack an overt in situ component. Whether this is the result of basal-like and triple-negative breast cancers progressing rapidly from DCIS to invasive cancer and/or obliterating the DCIS precursor from which they arose remains a matter of speculation.…”
Section: Precursors Of Basal-like and Triple-negative Cancersmentioning
confidence: 99%
“…Depending on the methodology and study population, AR positivity in breast carcinomas has been reported ranging from 50% to 90%, with the similar staining intensity as ER [11][12][13] . While most of the ER-positive breast carcinomas are also positive for AR [14] , AR is also positive in some of the triple negative and high grade breast carcinomas, even though the reported percentage is considerably variable among different studies (ranging from 0-53%) [11,12,[14][15][16][17] . Furthermore, studies have shown that the AR expression in breast carcinomas is clinically relevant.…”
mentioning
confidence: 99%